Multi-wavelength achromatic bifocal metalenses with controllable polarization-dependent functions for switchable focusing intensity. (10th December 2021) - Chen, Long; Shao, Zhenglong; Liu, Jia; Tang, Dongliang
Abstract: In this paper, a bifocal metalens is designed through simultaneously controlling two polarization-dependent functions, which can respectively focus x-polarized and y-polarized light into different positions, and the relative intensity between two foci can be continuously tuned through a simple rotation of the incident linear polarization angle. The proposed metalenses are composed of rectangle nanopillars with spatially varying widths and lengths, which provide distinct propagating phases under two orthogonal polarizations. Therefore, there exists a degree of freedom to achieve two polarization-dependent focusing functions. More importantly, these nanopillars possess excellent dispersion engineering, and provide an effective method for the realization of achromatic bifocal metalenses. After powerful optimizations, two achromatic bifocal metalenses are constructed and further demonstrated numerically. The x-polarized and y-polarized components are focused into different positions under different working wavelengths. Simulated results agree well with our designs. The approach here is expected to find optical applications in micro-manipulation, optical communication and multicolor display.